Uniaxial Stress-Strain Behavior for Material Pavement Stabilization by Using Zeolite - Hamzani Hamzani; Munirwansyah Munirwansyah; Muttaqin Hasan; Sugiarto Sugiarto; Burhanuddin Burhanuddin; Yovi Chandra (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
The characteristics of semi-flexible pavement (SFP) are strongly influenced by the proportion of cement mortar content filling the voids in the mixture. SFP behavior due to repeated traffic loads causes the pavement structure to experience stress and strain around the wheel axis, resulting in a rapid decline in performance with cracks and permanent defects. Evaluation of the properties of the mixture on the stress-strain parameters of the influence of additives and substitution of many SFP mixture-forming materials has been carried out. The purpose of this study was to determine the stress-strain models of SFP with the effect of waste tire rubber (WTR) additives in asphalt and Aceh natural zeolite substitution in cement mortar under uniaxial compressive load. The porous asphalt mixture is designed in accordance with the optimum asphalt content and open graded aggregate based on the specifications of Bina Marga Regulation 2010 and Australian Asphalt Pavement (AAPA) 2004. The composition of zeolite in SFP mixture can affect the stress behavior, where zeolite can inprove quality of the mortar cement so that it can slow down the development of the SFP mixture flatness and the maximum stress obtained is 17 MPa at 5% zeolite composition. The bilinear model of stress-strains was proposed the results show a good agreement with experimental results.